Almost layer finiteness of a periodic group without involutions - Senashov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove a theorem that characterizes the class of almost layer finite groups in the class of periodic groups without involutions: If the normalizer of any nontrivial finite subgroup of a periodic conjugate biprimitive finite group without involutions is almost layer finite, then the group itself is almost layer finite.